Fault tolerance for hypercube networks via independent spanning trees - Umrao L.S.; Mahato D.P.; Singh R.S. (My University, 2025)
Independent spanning trees (ISTs) may be used for message broadcasting in any interconnection networks, which provides preferential performances. It can be used to enhance the fault tolerance, bandwidth, and security. In this way, the designs of ISTs for various types of topologies have been widely analysed. There is a hypothesis on ISTs: any n-connected network has n ISTs rooted at any node. In this paper, we first analysed the algorithm then parallel construct the ISTs in hypercubes. We give an algorithm for ISTs which can be applied to solve any node broadcast problem for hypercubes. Then, simulation results showed that fault tolerance is effective in reliable broadcasting and concedes 11%-23% fault tolerance for successful broadcasting. © 2014 IEEE.